Combined Transarterial Chemoembolization and Radiofrequency Ablation for Hepatocellular Carcinoma Infeasible for Ultrasound-Guided Percutaneous Radiofrequency Ablation: A Comparative Study with General Ultrasound-Guided Radiofrequency Ablation Outcomes - Cha, Dong Ik; Lee, Min Woo; Hyun, Dongho; Ahn, Soo Hyun; Jeong, Woo Kyoung; Rhim, Hyunchul (Cancers, 2023)
Objectives: This study aimed to evaluate the therapeutic outcomes of transarterial chemoembolization combined with radiofrequency ablation (TACE + RFA) for hepatocellular carcinomas (HCC) measuring ≤3 cm infeasible for ultrasound (US)-guided percutaneous RFA. Methods: Twenty-four patients who underwent fluoroscopy-guided TACE + RFA for single HCC between January 2012 and December 2016 were screened. To evaluate the TACE + RFA outcomes compared with those of US-guided RFA, 371 patients who underwent US-guided RFA during the same period were screened. We compared local tumor progression (LTP) and intrahepatic distant recurrence (IDR) between the two groups before and after propensity score (PS) matching, and performed univariable and multivariable Cox proportional hazard regression analyses for all patients. Results: PS matching yielded 21 and 42 patients in the TACE + RFA and US-guided RFA groups, respectively. Cumulative LTP rates after PS matching were not significantly different between the two groups at 1 (0.0% vs. 7.4%, p = 0.072), 2 (10.5% vs. 7.4%, p = 0.701), and 5 years (16.9% vs. 10.5%, p = 0.531). IDR rates did not differ significantly between the two groups at 1 (20.6% vs. 10%, p = 0.307), 2 (25.9% vs. 25.9%, p = 0.999), or 5 years (49.9% vs. 53%, p = 0.838). Multivariable analysis showed that treatment type was not a significant factor for LTP or IDR. Conclusion: The outcomes of TACE + RFA for HCC were similar to those of general US-guided RFA. Fluoroscopy-guided TACE + RFA may be an effective treatment when US-guided RFA is not feasible.
Keywords: carcinoma; chemoembolization; fluoroscopy; hepatocellular; radiofrequency ablation